Mechanism of normal menstruation and abnormality associated with menorrhagia (Medical Journal of Indonesia, 2001)
Normal menstruation involves endometrial tissue breakdown and bleeding, followed by hemostasis and repair. Abnormality of this process at any stage may result in changes in the quantity of menstrual blood loss. When menstrual blood loss is greater than 80 ml, it is called menorrhagia. This review discuss the mechanism of normal menstruation, and factors associated with menorrhagia. Those factors are the endometrial bleeding associated factor (ebaf), the role of various cells (migratory leucocytes, macrophages, and mast cells), the role of various substances (lysosomal enzymes, prostaglandins, endothelins, growth factors and its receptors), impairment of fibrinolysis and hemostatic proces, and changes in endometrial blood flow. (Med J Indones 2001; 10: 121-6) Keywords : ebaf, prostaglandin, endothelin, fibrinolysis